Childhood interstitial lung disease: Family experiences. Issue 12 (4th March 2015) - Gilbert, Carlee; Bush, Andrew; Cunningham, Steve
Summary: Aims: To present experiences of UK families of children diagnosed with ILD, to inform clinical practice and service development. Methods: Thirty seven such families completed an anonymous web‐based survey between February and March 2014. Results: Median time from first symptoms to diagnosis was 25 weeks. Most reported that they were happy with the overall management of their child. Areas highlighted for development included improved communication especially the need for written information; psychological support (91% reported anxiety). Feeding issues (not described in current literature) were reported by 77% and persisted in 35%. Other requests included better written communication between hospitals with training for smaller hospitals, and improved specialist nurse support for children with ILD. Conclusions: These family perspectives need to be addressed by professionals looking after these children as well as when planning of future services.Pediatr Pulmonol. 2015; 50:1301–1303. © 2015 Wiley Periodicals, Inc.